2019
DOI: 10.1111/imj.14081
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of corticosteroid compared with non‐corticosteroid therapy for the treatment of drug‐induced acute interstitial nephritis: a systematic review

Abstract: The limited evidence does not support the use of corticosteroids in the treatment of DI-AIN. Larger, well-designed trials are needed to help guide clinical management of this condition. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
(104 reference statements)
0
8
0
Order By: Relevance
“…The use of corticosteroids in the treatment of DI-AIN is controversial and has not demonstrated consistent benefit. 5 , 20 Some studies have shown improvement of kidney function recovery with early initiation of corticosteroid therapy. 17 , 20 DI-AIN is a T-cell-mediated hypersensitivity reaction, and the suppressor effect of steroids on T cells and eosinophils may control inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of corticosteroids in the treatment of DI-AIN is controversial and has not demonstrated consistent benefit. 5 , 20 Some studies have shown improvement of kidney function recovery with early initiation of corticosteroid therapy. 17 , 20 DI-AIN is a T-cell-mediated hypersensitivity reaction, and the suppressor effect of steroids on T cells and eosinophils may control inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…5 , 20 Some studies have shown improvement of kidney function recovery with early initiation of corticosteroid therapy. 17 , 20 DI-AIN is a T-cell-mediated hypersensitivity reaction, and the suppressor effect of steroids on T cells and eosinophils may control inflammation. 3 The lack of high-quality randomized controlled trials regarding the use of corticosteroids in the treatment of DI-AIN suggests that more research should be performed.…”
Section: Discussionmentioning
confidence: 99%
“…[2427] In a recent research, Quinto LR et al made a systemic review of 8 retrospective studies comparing the effects of corticosteroid therapy versus non-corticosteroid therapy in the treatment of drug induced AIN. [28] Four studies showed no difference in serum creatinine between corticosteroid and non-corticosteroid therapy, while 4 studies found a benefit of corticosteroid therapy. Regretfully, a meta-analysis was not performed due to considerable heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…1 We weren't able to metaanalyse these studies because of their considerable heterogeneity and low quality of evidence, but it is noteworthy that they included a total of just 430 patients, 300 treated with corticosteroids and 130 with other, poorly-defined treatments (Table 1). 1 The literature since the systematic review is notable for one randomized trial (which compared oral with intravenous corticosteroid therapy), two retrospective analyses which added a further 295 patients to the literature, with 274 patients receiving corticosteroids. [2][3][4] The epidemiological features lacking in the literature; prospective patient recruitment, control groups and randomization, are critical in the setting of DI-AIN.…”
Section: The Evidencementioning
confidence: 99%